(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article provides a comprehensive analysis of psychological and pedagogical approaches aimed at effectively organizing and developing students’ learning processes in teaching literary knowledge in literature lessons. Theoretical and practical principles necessary to support students’ intellectual and emotional development are developed.